Q: How is -6k plus 7k simplified?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-6k + 7k = k

k + 6k - 13 = 177k = 30k = 30/7k = 4.2857

26-7k=6k First, add 7k to get k on one side. 26-7k+7k=6k+7k 26=13k Divide both sides by 13 to get k by itself. 26/13=13k/13 2=k The answer is 2.

Same as subtracting 6 from 7 = K

7(k + 5)(k - 4)

Related questions

-6k + 7k = k

1k

-6k+7k = 1k or normally k on its own.

7k + 4 + 4k - 9 - 5k (7k + 4k - 5k) + (4 - 9) 6k + -5 6k - 5

The answer is 13k .

-6k + 7k = k or 7k- 6k = k or Factor out 'k' k(-6 + 7) = k(1) = k

k + 6k - 13 = 177k = 30k = 30/7k = 4.2857

26-7k=6k First, add 7k to get k on one side. 26-7k+7k=6k+7k 26=13k Divide both sides by 13 to get k by itself. 26/13=13k/13 2=k The answer is 2.

1k

do it yourself

Same as subtracting 6 from 7 = K

The given expression can be simplified to: 14k-12